Omega-3 Therapy Is Associated With Reduced Gastrointestinal Bleeding in Patients With Continuous-Flow Left Ventricular Assist Device. (October 2018) - Imamura, Teruhiko; Nguyen, Ann; Rodgers, Daniel; Kim, Gene; Raikhelkar, Jayant; Sarswat, Nitasha; Kalantari, Sara; Smith, Bryan; Chung, Ben; Narang, Nikhil; Juricek, Colleen; Burkhoff, Daniel; et al.
Abstract : Background: Gastrointestinal bleeding (GIB) is a common complication seen in patients supported with left ventricular assist devices (LVADs) and is related to increased inflammation and angiogenesis. Omega-3 is an unsaturated fatty acid that possesses anti-inflammatory and antiangiogenic properties. This study aims to assess the prophylactic efficacy of treatment with omega-3 on the incidence of GIB in LVAD patients. Methods and Results: Among consecutive 166 LVAD patients enrolled in this analysis, 30 patients (49 years old and 26 male) received 4 g/d of omega-3 therapy for 310±87 days and 136 patients in the control group (58 years old and 98 male) were observed for 302±102 days. One-year GIB-free rate was significantly higher in the omega-3 group as compared with the control group (97% versus 73%; P =0.02). Omega-3 therapy was associated with the occurrence of GIB in both the univariate (hazard ratio, 0.12; 95% CI, 0.02–0.91; P =0.040) and multivariate Cox proportional hazard ratio analyses (hazard ratio, 0.13; 95% CI, 0.02–0.98; P =0.047). The frequency of GIB was significantly lower in the omega-3 group (0.08±0.42 versus 0.37±0.93 events/y; P =0.01), accompanied by significantly lower blood product transfusion and shorter days in the hospital. The frequency of GIB remained lower among the omega-3 group after matching for patient background characteristics (96% versus 73%, P =0.028). Conclusions: LVAD patients treated with omega-3 had a significant increase in freedom from GIB. A randomized controlled study is warranted to evaluate the use of omega-3 in LVAD patients. Abstract : Supplemental Digital Content is available in the text.